Learnings, Issues, and Challenges Encountered by Students and Faculty Members in the Implementation of Small Private Online Courses (SPOCs) - Geronimo, Cecilia A.; Adriano, Raquel C.; Celestino, Joseph Roy F. (Future Science / FSH-PH Publications, 2024)
Consistent with the Plan-Do-Check-Act (PDCA) design of ISO 9001:2015, performance evaluation of policies pertaining to the University’s main functions, i.e., instruction, research, and extension, should be pursued, especially for a newly implemented policy. Small Private Online Courses (SPOCs) at Bulacan State University were crafted, developed, and enhanced not only in compliance with the demands of continuing education but also to suit the standard of learning that is equal to classroom instruction catered physically. Whether these courses became effective and efficient within the duration of implementation remains to be determined. In the hope of having a fair and honest assessment that willlead towards relevant refinement of offering SPOCs, this mixed method of research undertaking aims to re-examine its efficiency and effectiveness, specifically, the learnings, issues and challenges encountered by the facultymembers and students when using SPOC as modality. Thesurvey questionnaire and interview questions were developed and validated and the interview among faculty members were face to face while the survey questionnaire for the SPOC students was through Google form for answering online, and the respondents were five thousand and eight students and twenty-five faculty members were interviewed. The findings indicate the factors that may impede the success of the implementation of SPOCs, aside from personal logistic challenges, the lack of discipline to manage time and sustain the interest in a given lesson are problems that require attention and further innovation. While connectivity can be identified as a personal logistic challenge, it can also be a challenge on the part of the University. The problem of connectivity may be seen as an opportunity for the University to create its own Learning Management System that can be customized to suit fit according to bandwidth, accessible and affordable to students. It can be concluded that SPOC is a promising learning platform in a world where hybrid interactions are highly relevant and can help save a lot of time and resources which brings in the recommendation to revisit, redesign, and recalibrate it for the ever-changing landscape of education.